In search of equality : the Chinese struggle against discrimination in nineteenth-century America - McClain, Charles J., 1943- (University of California Press, 1994)
This illuminating volume probes the efforts of the Chinese community to battle the manifold kinds of discrimination encountered at the hands of government during the nineteenth century. Contrary to the stereotypical image of a passive, uninvolved, and insular group, the population revealed by Charles McClain is politically savvy and familiar with American political institutions, resentful of discriminatory treatment and capable of mobilizing to fight it. He draws on English- and Chinese-language documents, court files, and other sources to chronicle the ways the Chinese sought redress and change. McClain focuses on California, the home of the overwhelming majority of Chinese during the nineteenth century and the heart and hub of the anti-Chinese movement, and on the numerous cases the Chinese brought in the state and federal courts to vindicate their claim to equality of treatment under the law. In the 1862 case of Lin Sing v. Washburn, the California Supreme Court nullified a law imposing an onerous tax only on Chinese immigrants and aimed at discouraging Chinese immigration. An 1885 lawsuit by Joseph Tape, a Chinese parent, challenging the exclusion of Chinese children from the public schools, led to an order admitting his child. An 1890 measure attempted to remove San Francisco's Chinese residents from Chinatown and ghettoize them in a less desirable part of the city - the first attempt by an American municipality to segregate its inhabitants on the basis of race. Ten years later, after the discovery of suspected cases of bubonic plague in Chinatown, an attempt was made to force the Chinese to be inoculated with an experimental antiplague vaccine. These measures, too, were challenged by the Chinese and eventually struck down in the courts. In their battles for justice, the Chinese community helped to clarify a panoply of judicial issues, including the parameters of the Fourteenth Amendment and the legal meanings of nondiscrimination and equality. Discussing a wide-ranging set of court cases and gleaning their larger constitutional significance, In Search of Equality brings to light an important chapter of American cultural and ethnic history. It will attract attention from legal historians, scholars of Asian America, and historians of the American West.